Subacute sclerosing panencephalitis in Northern Ireland: twenty years' experience - Morrow, J I (1986)
Subacute sclerosing panencephalitis (SSPE) is a rare degenerative disease of the central nervous system that affects primarily children and adolescents. It is a late manifestation of measles virus infection. In a 20-year period (1965-85) there have been 26 cases of SSPE in Northern Ireland, a frequency of approximately one case per 1.2 million population per year. Males were affected more frequently than females. In other parts of the world the incidence of this disease has been dramatically reduced following effective measles immunisation programmes. The vaccination rate in Northern Ireland probably remains too low to have a similar effect.